Reviews of recent publications (Studies in 20th & 21st Century Literature, 2013)
David Palumbo-Liu. The Deliverance of Others: Reading Literature in a Global Age. by Paul Cahill Natalie Edwards. Shifting Subjects. Plural Subjectivity in Contemporary Francophone Women’s Autobiography by Anna Rocca Zsuzsu Baross. Posthumously: For Jacques Derrida by Stephen Barker Natalie Edwards, Amy L. Hubbell, and Ann Miller, eds. Textual and Visual Selves by Rachel Gabara Stephen M. Hart. Gabriel García Márquez by Regina Janes Vivian Liska. When Kafka Says We: Uncommon Communities in German-Jewish Literature by Tyler Whitney
Keywords: book review; German-Jewish Literature; Kafka; Selves; Textual Selves; Visual Selves; Derrida; Jacques Derrida; Women& #x27; s Autobiography; Plural Subjectivity; global; global age; francophone